Enamel repair material based on tannic acid as well as preparation method and application of enamel repair material

Through the tannin-based enamel repair material, combined with photothermal action, the problems of enamel remineralization and antibacteriality are solved, and the regeneration and repair of enamel and caries prevention are achieved, providing rapid and complex oral health without complex equipment. Solution.

CN119280397APending Publication Date: 2025-01-10WENZHOU MEDICAL UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411288921.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Enamel lacks regeneration and repair capabilities after injury, and the prior art is difficult to effectively realize the remineralization of enamel, and cannot effectively kill cariogenic bacteria and change the acidic microenvironment.

Method used

Using tannin-based enamel repair materials, mix ferric chloride and tannin solution through ultrasonic shock treatment, adjust pH, add calcium chloride and phosphate to form a TFA solution, and combine photothermal action to achieve remineralization of enamel. and antibacterial effects.

Benefits of technology

Effectively improve the regeneration and repair ability of enamel, prevent the progress of caries, has excellent antibacterial effects, and can quickly implement treatment in dental clinics without the need for complex equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119280397A_ABST
    Figure CN119280397A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of dental restoration, in particular to a tannic acid-based enamel restoration material as well as a preparation method and application thereof, and the preparation method comprises the following steps: step 1, adding water into tannic acid TA to prepare a TA solution with the concentration of 7.5-15mg / mL; 2, preparing a ferric chloride solution, mixing the ferric chloride solution with a TA solution, and carrying out ultrasonic oscillation treatment; 3, alkali liquor is added into the solution obtained after ultrasonic oscillation treatment in the step 2 to adjust the pH to 5.8-6.2, and a TF solution is obtained; 4, preparing a calcium chloride solution, and mixing the calcium chloride solution with the TF solution obtained in the step 3 to obtain a mixed solution A; and 5, preparing a phosphate solution, and mixing the phosphate solution with the mixed solution A to form the enamel repair material TFA solution. According to the invention, the regeneration and repair capability of tooth enamel can be effectively improved, the tooth enamel is remineralized, the progress of early caries is prevented, and an innovative solution is provided for the field of oral health.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of tooth restoration, and in particular to a tannic acid-based tooth enamel restoration material and a preparation method and application thereof. Background Art

[0002] Dental caries is a type of chronic loss of dental hard tissue caused by acid produced by cariogenic bacteria (such as Streptococcus mutans). It can cause changes in tooth color, gloss and morphology, and in severe cases even cause pulp and periapical inflammation, resulting in a large burden on life and economy. Currently, hundreds of millions of people are troubled by dental caries, making it a serious global public health problem. However, mature tooth enamel is composed of 96%-97% inorganic hydroxyapatite (HA, Ca 10 (PO4)6(OH)2), 3wt% water and 1wt% organic matter. It is a decellularized, avascular, highly mineralized tissue. It is the hardest tissue in the human body. Therefore, it lacks sufficient regeneration and repair ability after injury. 2+ and PO4 3- Therefore, to achieve meaningful remineralization, it is necessary not only to kill caries-causing bacteria on the enamel surface and change the acidic microenvironment, but also to provide sufficient Ca 2+ and PO4 3- ion.

[0003] Amorphous calcium phosphate (ACP) is the precursor of biogenic hydroxyapatite (HA) in bones and teeth and is the basic mineralization unit in the biomineralization process. 2+ and PO4 3 ions, but Ca 2+ and PO4 3- The ions will aggregate rapidly in a short period of time, and their crystal phase and structure will change to form stable HA. Therefore, it is difficult to achieve enamel remineralization with ACP solution alone.

[0004] Therefore, to prevent Ca 2+ and PO4 3- In order to achieve enamel remineralization through aggregation, it is necessary to construct a tannic acid-based enamel repair material to achieve enamel remineralization, so that it can be used as an important oral repair material to provide better protection for people's oral health. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a tannic acid-based tooth enamel repair material and a preparation method and application thereof to achieve tooth enamel remineralization.

[0006] Based on the above purpose, the present invention provides a method for preparing a tannic acid-based tooth enamel repair material, comprising the following steps:

[0007] Step 1: Add water to tannic acid TA to prepare a TA solution with a concentration of 7.5-15 mg / mL;

[0008] Step 2: prepare a ferric chloride solution and mix it with a TA solution, and then perform ultrasonic vibration treatment; wherein the mass ratio of ferric chloride to tannic acid TA is 4.8-6:75-150;

[0009] Step 3: Add alkali solution to the solution after ultrasonic oscillation treatment in step 2 to adjust the pH to 5.8-6.2 to obtain TF solution;

[0010] Step 4: prepare a calcium chloride solution and mix it with the TF solution obtained in step 3 to obtain a mixed solution A;

[0011] Step 5: preparing a phosphate solution, and then mixing it with the mixed solution A to form a tooth enamel repair material TFA solution;

[0012] The concentration of calcium ions in the TFA solution is 1.6-3.2 mM, and the concentration of phosphate ions is 0.96-1.92 mM.

[0013] Preferably, the ferric chloride solution prepared in step 2 is prepared by dissolving ferric chloride hexahydrate in deionized water.

[0014] Preferably, in step 2, the 750W ultrasonic oscillation treatment time is 3-7 minutes, preferably 5 minutes.

[0015] Optionally, the alkali solution in step 3 is sodium hydroxide and / or potassium hydroxide solution. The alkali solution is preferably sodium hydroxide solution.

[0016] Preferably, the calcium chloride solution prepared in step 4 is prepared by dissolving calcium chloride dihydrate in deionized water.

[0017] Optionally, the phosphate in step five includes dipotassium hydrogen phosphate, disodium hydrogen phosphate, potassium hydrogen phosphate, and sodium hydrogen phosphate.

[0018] Preferably, in step five, the phosphate is dipotassium hydrogen phosphate.

[0019] Preferably, the molar ratio of calcium ions to phosphate ions in the TFA solution is 5:3.

[0020] The invention also provides a tannic acid-based tooth enamel repair material, which is prepared by the preparation method.

[0021] The present invention also provides application of the tannic acid-based tooth enamel repair material in oral medicine or mouthwash.

[0022] Beneficial effects of the present invention:

[0023] 1. The present invention successfully constructs a tannic acid-based tooth enamel repair material, namely a tannic acid-based two-in-one photothermal and remineralization system, which can effectively improve the regeneration and repair ability of tooth enamel, remineralize tooth enamel, and prevent the progression of early caries.

[0024] 2. It not only promotes the remineralization of tooth enamel, but also has excellent antibacterial effects, which helps eliminate the bacteria that cause caries and reduce the risk of infection.

[0025] 3. It provides innovative solutions for the field of oral health, allowing for quick implementation of treatments in dental clinics without the need for complex equipment or procedures. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 : is the infrared spectra of TA, TF and TFA of the present invention;

[0028] Figure 2 is the X-ray diffraction (XRD) pattern of TFA of the present invention;

[0029] Figure 3 is the SAED pattern of TFA of the present invention;

[0030] Figure 4 This is a temperature curve diagram of the TFA photothermal experiment of the present invention;

[0031] Figure 5 It is the bacterial residue analysis of the TFA antibacterial experiment of the present invention;

[0032] Figure 6 This is the antibacterial rate analysis of the TFA antibacterial experiment of the present invention;

[0033] Figure 7 This is the remineralization morphology analysis of the TFA remineralization experiment of the present invention. DETAILED DESCRIPTION

[0034] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0035] It should be noted that, unless otherwise defined, the technical terms or scientific terms used in the present invention should be understood by people with ordinary skills in the field to which the present invention belongs. The words "include" or "comprise" and the like used in the present invention mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, but do not exclude other elements or objects.

[0036] The present invention relates to a tannic acid-based tooth enamel repair material, which is obtained according to the following preparation steps:

[0037] Step 1: Mix 75-150 mg of tannic acid TA with 10 ml of deionized water to form a TA solution;

[0038] Step 2: Take 8-10 mg of ferric chloride hexahydrate FeCl3.6H2O and dissolve it in deionized water to obtain a mixed solution, then mix the mixed solution with the TA solution and perform ultrasonic oscillation treatment;

[0039] Step 3: After ultrasonic vibration, use sodium hydroxide NaOH solution to adjust the pH to 6, and then add deionized water until the total solution volume is 30 ml to obtain TF solution;

[0040] Step 4: Take 11.76-23.52 mg of calcium chloride dihydrate CaCl2·2H2O and add it to 10 ml of deionized water, and then mix it with the TF solution obtained in step 3 to obtain a mixed solution;

[0041] Step 5: Dissolve 8.352-16.704 mg of potassium dihydrogen phosphate K2HPO4 in 10 ml of deionized water, and then mix it with the mixed solution obtained in step 4 to form a TFA solution of enamel repair material. 2+ The concentration of phosphate ion PO4 is 1.6-3.2mM 3- The concentration is 0.96-1.92mM.

[0042] The main materials and reagents used in the embodiments of the present invention are as follows:

[0043] Tannic acid TA, ferric chloride hexahydrate (FeCl 3 .6H2O), sodium hydroxide (NaOH), calcium chloride dihydrate (CaCl2·2H2O), and potassium hydrogen phosphate (K2HPO4) were purchased from Aladdin Reagent (Shanghai, China).

[0044] Example 1

[0045] A tannic acid-based tooth enamel repair material is prepared according to the following steps:

[0046] a. Mix 100 mg TA and 20 ml deionized water to form a TA solution;

[0047] b. Take 10 mg of ferric chloride hexahydrate FeCl3.6H2O and dissolve it in deionized water to obtain a mixed solution. Then mix the mixed solution with the TA solution and perform ultrasonic oscillation treatment at 750W for 5 minutes.

[0048] c. After ultrasonic vibration, use sodium hydroxide NaOH solution to adjust the pH to 6, and then add deionized water until the total solution volume is 30 ml to obtain TF solution;

[0049] d. Take 17.64 mg of calcium chloride dihydrate CaCl2·2H2O and add it to 10 ml of deionized water, and then mix it with the TF solution obtained in step 3 to obtain a mixed solution;

[0050] e. Take 12.528 mg of potassium dihydrogen phosphate K2HPO4 and dissolve it in 10 ml of deionized water, then mix it with the mixed solution obtained in d to form enamel repair material TA-Fe III -ACP(TFA) solution.

[0051] At this time, the calcium ion concentration is 2.4mM and the phosphate ion concentration is 1.44mM, of which Ca 2+ With PO4 3- The molar ratio is 5:3.

[0052] The tooth enamel repair material TFA constructed based on tannic acid in the present invention can integrate Ca 2+ Prevent it from interacting with PO4 3- Aggregation can stabilize ACP, and at the same time, infrared irradiation can achieve photothermal antibacterial and realize enamel remineralization.

[0053] See also Figure 1 , ACP solution can pass through 563cm -1 The presence of TA can be identified by the bending vibration peak at , which confirms that TA binds to ACP and maintains the amorphous phase of the latter. 2+ When the nanocomposites are formed by interaction, the tensile vibration peak is at 3400 cm -1 The forward movement of TA and Ca 2+ Chelation.

[0054] See also Figure 2 The X-ray diffraction (XRD) pattern of TFA exhibits a broad band at about 2θ = 25°, indicating its lack of long-range periodicity, thus ruling out the presence of HAp or other CaP crystalline phases.

[0055] See also Figure 3, SAED showed no special dot or ring pattern, indicating that TFA was in an amorphous phase, and thus the synthesis was successful.

[0056] Example 2

[0057] A tannic acid-based tooth enamel repair material is prepared according to the following steps:

[0058] a. Mix 100 mg TA and 20 ml deionized water to form a TA solution;

[0059] b. Take 10 mg of ferric chloride hexahydrate FeCl3.6H2O and dissolve it in deionized water to obtain a mixed solution. Then mix the mixed solution with the TA solution and perform ultrasonic oscillation treatment at 750W for 5 minutes.

[0060] c. After ultrasonic vibration, use sodium hydroxide NaOH solution to adjust the pH to 6, and then add deionized water until the total solution volume is 30 ml to obtain TF solution;

[0061] d. Take 11.76 mg of calcium chloride dihydrate CaCl2·2H2O and add it to 10 ml of deionized water, and then mix it with the TF solution obtained in step 3 to obtain a mixed solution;

[0062] e. Take 8.352 mg of potassium dihydrogen phosphate K2HPO4 and dissolve it in 10 ml of deionized water, then mix it with the mixed solution obtained in d to form enamel repair material TA-Fe III -ACP(TFA) solution.

[0063] At this time, the calcium ion concentration is 1.6mM and the phosphate ion concentration is 0.96mM, of which Ca 2+ With PO4 3- The molar ratio is 5:3.

[0064] The tooth enamel repair material TFA constructed based on tannic acid in the present invention can integrate Ca 2+ Prevent it from interacting with PO4 3- Aggregation can stabilize ACP, and at the same time, infrared irradiation can achieve photothermal antibacterial and realize enamel remineralization.

[0065] Example 3

[0066] A tannic acid-based tooth enamel repair material is prepared according to the following steps:

[0067] a. Mix 100 mg TA and 20 ml deionized water to form a TA solution;

[0068] b. Take 10 mg of ferric chloride hexahydrate FeCl3.6H2O and dissolve it in deionized water to obtain a mixed solution. Then mix the mixed solution with the TA solution and perform ultrasonic oscillation treatment at 750W for 5 minutes.

[0069] c. After ultrasonic vibration, use sodium hydroxide NaOH solution to adjust the pH to 6, and then add deionized water until the total solution volume is 30 ml to obtain TF solution;

[0070] d. Take 23.52 mg of calcium chloride dihydrate CaCl2·2H2O and add it to 10 ml of deionized water, and then mix it with the TF solution obtained in step 3 to obtain a mixed solution;

[0071] e. Take 16.704 mg of potassium dihydrogen phosphate K2HPO4 and dissolve it in 10 ml of deionized water, then mix it with the mixed solution obtained in d to form enamel repair material TA-Fe III -ACP(TFA) solution.

[0072] At this time, the calcium ion concentration is 3.2mM and the phosphate ion concentration is 1.92mM, of which Ca 2+ With PO4 3- The molar ratio is 5:3.

[0073] The tooth enamel repair material TFA constructed based on tannic acid in the present invention can integrate Ca 2+ Prevent it from interacting with PO4 3- Aggregation can stabilize ACP, and at the same time, infrared irradiation can achieve photothermal antibacterial and realize enamel remineralization.

[0074] The product obtained in Example 1 was tested as follows:

[0075] 1. Photothermal experiment

[0076] Take 1 ml of TFA solution (TA concentration is 2 mg / ml) and measure the concentration of each sample at 808 nm and 1.5 W / cm 2 Irradiate with infrared light for 300 seconds, measure the temperature every 30 seconds using an infrared camera, and test according to the above method on days 1, 3, 5, and 7.

[0077] result:

[0078] See also Figure 4 :1ml TFA solution at 808nm, 1.5W / cm 2 After being irradiated with infrared light for 300s, the temperature can rise to above 50℃ in 1, 3, 5, and 7 days.

[0079] 2. Antibacterial test

[0080] 1. Take a single colony of S. mutans and culture it in brain heart infusion (BHI) medium at 37°C for 24 hours; the bacterial concentration obtained is about 10 8 CFU / mL (15ml centrifuge tube 4ml culture medium). Centrifuge at 5000rpm for 5min to obtain bacterial pellet, and resuspend in 4ml PBS solution.

[0081] 2. Dilute the bacteria 100 times and control the concentration at 10 6 CFU / mL, and then the obtained bacterial suspension (100 μL, 10 6 CFU / mL) were mixed with 100 μL PBS, TFA (TA concentration of 1.75 mg / ml), TFA (TA concentration of 2 mg / ml), and TFA (TA concentration of 2.25 mg / ml) in a 2 mL test tube. -2 The suspension was irradiated for 5 min.

[0082] Finally, the mixture was serially diluted 10 1 , 10 2 , 10 3 , 10 4 5ul of the solution was taken and plated respectively, and cultured at 37℃ for 24h. The number of colonies was counted and the number of remaining bacteria was expressed as log 10x to calculate the antibacterial rate.

[0083] result:

[0084] See also Figure 5 and Figure 6 : At the concentrations of TA (1.75, 2, 2.25), the antibacterial rate can reach 100% after 5 minutes of illumination, indicating that the photothermal antibacterial property of TFA solution is good.

[0085] 3. Remineralization experiment

[0086] In the demineralized enamel preparation, the enamel samples were etched with 37% phosphoric acid, then rinsed and sonicated for 5 minutes to remove residual crystals. The sample surface was coated with 100 μL of deionized water and TF, CPP-ACP (2%) and TFA solution, then immersed in 5 mL of sterile artificial saliva at 37°C and irradiated with 808 nm infrared light for 5 minutes. This treatment was repeated every 12 hours. In order to simulate the natural oral environment with a basically neutral pH, the remineralization effect of different solutions under neutral conditions was mainly explored. After 7 days of treatment, the samples were rinsed with deionized water and the degree of remineralization was characterized.

[0087] result:

[0088] See also Figure 7: The surface of demineralized enamel treated with TFA is smoother, while the surface of demineralized enamel treated with CPP-ACP and TF is still rougher. By comparison, it can be seen that the remineralization performance of TFA is better than that of CPP-ACP and TF.

[0089] In summary:

[0090] The present invention successfully constructs a tannic acid-based tooth enamel repair material, namely a tannic acid-based two-in-one system of light, heat and remineralization, which can effectively improve the regeneration and repair ability of tooth enamel, remineralize tooth enamel and prevent the progression of early caries. It not only promotes the remineralization of tooth enamel, but also has excellent antibacterial effects, helps to eliminate bacteria that cause caries and reduce the risk of infection. At the same time, it provides an innovative solution for the field of oral health, which can be quickly implemented in dental clinics without complicated equipment or procedures.

[0091] Those skilled in the art should understand that the discussion of any of the above embodiments is only exemplary and is not intended to imply that the scope of the present invention is limited to these examples; under the concept of the present invention, the technical features in the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other changes in different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity. Any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a tannic acid-based tooth enamel repair material, characterized in that: The steps include: Step 1: Add water to tannic acid TA to prepare a TA solution with a concentration of 7.5-15 mg / mL; Step 2: prepare a ferric chloride solution and mix it with a TA solution, and then perform ultrasonic vibration treatment; wherein the mass ratio of ferric chloride to tannic acid TA is 4.8-6:75-150; Step 3: Add alkali solution to the solution after ultrasonic oscillation treatment in step 2 to adjust the pH to 5.8-6.2 to obtain TF solution; Step 4: prepare a calcium chloride solution and mix it with the TF solution obtained in step 3 to obtain a mixed solution A; Step 5: preparing a phosphate solution, and then mixing it with the mixed solution A to form a tooth enamel repair material TFA solution; The concentration of calcium ions in the TFA solution is 1.6-3.2 mM, and the concentration of phosphate ions is 0.96-1.92 mM.

2. The method for preparing the tannic acid-based tooth enamel repair material according to claim 1, characterized in that: Step 2: The ferric chloride solution is prepared by dissolving ferric chloride hexahydrate in deionized water.

3. The method for preparing the tannic acid-based tooth enamel repair material according to claim 1, characterized in that: Step 2: The ultrasonic vibration treatment time is 3-7 minutes.

4. The method for preparing the tannic acid-based tooth enamel repair material according to claim 1, characterized in that: In step 3, the alkali solution is sodium hydroxide and / or potassium hydroxide solution.

5. The method for preparing the tannic acid-based tooth enamel repair material according to claim 1, characterized in that: Step 4: preparing the calcium chloride solution by dissolving calcium chloride dihydrate in deionized water.

6. The method for preparing the tannic acid-based tooth enamel repair material according to claim 6, characterized in that: The phosphate in step 5 includes dipotassium hydrogen phosphate, disodium hydrogen phosphate, potassium hydrogen phosphate, and sodium hydrogen phosphate.

7. The method for preparing the tannic acid-based tooth enamel repair material according to claim 1, characterized in that: In step 5, the phosphate is dipotassium hydrogen phosphate.

8. The method for preparing the tannic acid-based tooth enamel repair material according to claim 1, characterized in that: The molar ratio of calcium ions to phosphate ions in the TFA solution is 5:

3.

9. A tannic acid-based tooth enamel repair material, characterized in that: The method is prepared by any one of claims 1 to 8.

10. Use of the tannic acid-based tooth enamel repair material according to claim 9 in oral medicine or mouthwash.

Citation Information

Cited By

  • Antibacterial synergy-mineralization regulation difunctional nano material as well as preparation method and application thereof

    CN120713863A

  • A dual-functional nanomaterial for "antibacterial synergistic-mineralization regulation" and a preparation method and application thereof

    CN120713863B